Evaluation of waste materials in transportation engineering - Mersin, Denizhan (My University, 2022)
Nowadays, intensive work is being done on the evaluation of household waste and during the production of various products. This study compiles studies investigating the usability of wastes such as marble dust, fly ash, phosphogypsum, and glass dust in asphalt pavement mixtures. Marshall stability samples were prepared by using asphalt cement at 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, and 6.5 ratios to determine the optimum binder ratio. The optimum bitumen percentage was determined by applying the Marshall stability test to the prepared samples. Marshall stability test was applied to the samples for the optimum bitumen percentage found as 4.9%. The variation of Marshall stability and yield values in bituminous mixtures using industrial waste fillers were investigated. In addition, the usability of used engine oils in the modification of bituminous binders has also been mentioned. For this purpose, bitumen was modified by mixing horse engine oil in 5 different ratios ranging from 1% to 5% from 70/100 penetration class to bitumen using a standard method. The changes in the bitumen as a result of the modification were investigated on basic engineering properties such as penetration, softening, flash point, and viscosity. At the same time, it was revealed how the temperature sensitivity of the bitumen and the mixing and compaction temperatures changed after the bitumen was modified with used engine oil. In addition, the modification index is defined for each test method. As a result, a significant change has occurred in the basic engineering properties of the modified bitumen samples using different ratios of used engine oil additives. It was determined that the softening point, flash point, and viscosity values of the bitumen with an increase in the penetration value were decreased. According to the evaluations made on the basic engineering properties of bitumen, it was predicted that it would be possible to recycle used engine oils by using them in bitumen modification.
Bildiri - Yayımlanmış
Keywords: Environment; Civil engineering; Transportation engineering; Circular economy